HUMAN BONE MARROW AND ADIPOSE TISSUE DERIVED MESENCHYMAL STROMAL CELL INFLUENCE ON NEUROLOGICAL DEFICIT RECOVERY IN A MODEL OF SEVERE TRAUMATIC BRAIN INJURY IN RATS - E. V. Polovnikov; V. V. Stupak; A. G. Samokhin; I. A. Vasiliev; O. B. Dobryakova; E. Ya. Shevela; E. R. Chernykh (Acta Biomedica Scientifica, 2012)
In the present study we characterized the effect of transplantation of bone marrow and adipose tissue MSCs in the model of brain injury in rats. This study was performed on Wistar rats (males and females in equal proportions with body weight of 250—270 g; n = 50). Traumatic brain injury was produced, by original spring-loaded, mechanism to precise dosing of impact force. Neurological disorders were assessed by Chen scale, a vertical grid test and a Morris water maze. MSC injections on day 1 were accompanied by a significant reduction in neurological deficit in compare with the control group. Adipose tissue derived MSCs were found to have a more pronounced effectiveness than MSCs obtained from bone marrow.